2014
DOI: 10.1089/scd.2013.0642
|View full text |Cite
|
Sign up to set email alerts
|

Role of Notch Signaling in the Maintenance of Human Mesenchymal Stem Cells Under Hypoxic Conditions

Abstract: Human adipose tissue-derived multilineage progenitor cells (hADMPCs) are attractive for cell therapy and tissue engineering because of their multipotency and ease of isolation without serial ethical issues. However, their limited in vitro lifespan in culture systems hinders their therapeutic application. Some somatic stem cells, including hADMPCs, are known to be localized in hypoxic regions; thus, hypoxia may be beneficial for ex vivo culture of these stem cells. These cells exhibit a high level of glycolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…The cells may have compensated for reduced oxygen availability by shifting their metabolism more toward anaerobic glycolysis as glucose consumption and lactate production were both significantly higher in hypoxia. Similar hypoxic resiliency and metabolic shifts have been demonstrated in ASCs 26 and other cell types. 27,28 This finding is promising regarding the ability of ASCs to endure harsh ischemic environments after transplantation.…”
Section: Discussionsupporting
confidence: 71%
“…The cells may have compensated for reduced oxygen availability by shifting their metabolism more toward anaerobic glycolysis as glucose consumption and lactate production were both significantly higher in hypoxia. Similar hypoxic resiliency and metabolic shifts have been demonstrated in ASCs 26 and other cell types. 27,28 This finding is promising regarding the ability of ASCs to endure harsh ischemic environments after transplantation.…”
Section: Discussionsupporting
confidence: 71%
“…HES1 is a critical downstream effector of the Notch signaling pathway, and its activation regulates vascular remodeling and arterial fate of endothelial cells 38 . Importantly, activation of the Notch signaling pathway also increases human MSC survival 39 . Similarly, TCF4 is a key downstream effector of Wnt signaling, a canonical pathway that plays a central role in vascular development 40 and in determining and maintaining the phenotype and functional properties of human stem cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Physiologic oxygen tension ranges from £1% in cartilage and regions of the bone marrow to 10%-13% in the main arteries of most tissues [6]. Increasing evidence suggests that oxygen tension is a key regulator of cell growth, proliferation, senescence, and differentiation of stem and progenitor cells [4,[7][8][9][10][11][12][13]. We reported that low oxygen enhances MIAMI cell pluripotency, proliferation, and maintenance of osteoblastic differentiation capability [4].…”
Section: Introductionmentioning
confidence: 89%
“…Stem cell self-renewal involves several pathways, including Notch, Wnt, repressor element (RE)-1-silencing transcription factor (REST), Sirtuin, and the PI3K/Akt/mTOR pathway [13][14][15][16][17][18]. The highly conserved Notch pathway can regulate stem cell self-renewal [13,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation